Implementasi Teori Behavioris-Strukturalis dalam Pembelajaran Bahasa Arab - Arisnaini Arisnaini (2022)
Many theories about learning have developed from the 19th century to the present. At the beginning of the 19th century learning theory that developed rapidly and made many contributions to psychologists was the theory of learning behavior (behaviorism). Behaviorism learning theory is oriented towards measurable and observable results. Repetition and training are used so that the desired behavior can become a habit. The expected result from the application of this behavioristic theory is the formation of the desired behavior. Desired behavior gets positive reinforcement, inappropriate behavior gets negative rewards, and evaluations or assessments are based on visible behavior.